Characterizing emergency department patients who reported work‐related injuries and illnesses. Issue 8 (11th July 2016) - Bhandari, Ruchi; Marsh, Suzanne M.; Reichard, Audrey A.; Tonozzi, Theresa R.
Abstract : Background: Per a Congressional directive and funding, this study describes worker and workplace characteristics of emergency department (ED) patients who reported their injury/illness to their employer. The study also responds to Congress's request to enumerate injured/ill self‐employed workers and workers with chronic conditions. Methods: We conducted a follow‐back study on injured/ill workers, including self‐employed, identified from a national ED surveillance system from June 2012 through December 2013. Results: An estimated 3, 357, 000 (95%CI: 2, 516, 000–4, 199, 000) workers treated in EDs reported their injury/illness to their employer or were self‐employed. Of those, 202, 000 (95%CI: 133, 000–272, 000) had a chronic condition. Of all reporters, excluding self‐employed, 77% indicated they received instructions as to whom to report. Conclusion: The study did not identify underreporting issues and revealed that medical records data may not be appropriate for assessing underreporting. Additional research is needed to examine workplace characteristics that encourage injury and illness reporting. Am. J. Ind. Med. 59:610–620, 2016. © 2016 Wiley Periodicals, Inc.